Spotting the Environmental Effect of the Economy and Technology: How the Development is Causing A Stringency with Carbon Emission? - Yuaningsih, Lilis; Febrianti, R. Adjeng Mariana (International Journal of Energy Economics and Policy, 2021)
The increasing threat to natural climate has extended the focused on economic growth and technology. Thus, this research contribution has provided an empirical investigation for examining the impact of economic and science and technology indicators on carbon emission from five different sources namely; emission from transport industry, other sectors, residential building, electricity and heat production, and emission from manufacturing industries in Thailand. Different statistical analyses were done to analyze the individual and combine effect of both economic and science and technological indicators during 1990 to 2014 with yearly data trends. The results show that some economic factors are found to be positive determinants of carbon emission, while others have shown their adverse influence in increasing carbon threats to natural environment in Thailand. As per the research implications, present work is among the initial contribution while exploring the environmental effects of growth and technology in Thailand for which a specific research findings are presented earlier. For this reason, this work can provide a good understanding to policy-makers, reserachers, and students in the targeted fields like carbon emission, economy and science and technology. Moreover, some productive future directions are also provided in this paper. First, methodological context of the study can be revised for better findings through some time series models. Second, regional context of the study may spread to other economies like Indonesia, Malaysia and Singapore. Keywords: Climate change, carbon emission, economic growth, Thailand. JEL Classifications: O44, P18, Q56 DOI: https://doi.org/10.32479/ijeep.10938